2013
DOI: 10.3402/tellusa.v65i0.19245
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Iberian upwelling implied by ERA-40 and ERA-Interim reanalyses

Abstract: A B S T R A C T The Regional Ocean Modeling System ocean model is used to simulate the decadal evolution of the regional waters in offshore Iberia in response to atmospheric fields given by ECMWF ERA-40 (1961Á2001) and ERAInterim (1989Á2008) reanalyses. The simulated sea surface temperature (SST) fields are verified against satellite AVHRR SST, and they are analysed to characterise the variability and trends of coastal upwelling in the region. Opposing trends in upwelling frequency are found at the northern li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…Importantly, there is stronger agreement that significant trends of upwelling intensification are evident at higher latitude for all EBUS. Among studies excluded from the meta-analysis, either because they did not meet the strict selection criteria or because they were published after the analysis was completed, most (Di Lorenzo et al, 2005;Alves and Miranda, 2013;Barton et al, 2013;Bylhouwer et al, 2013;Stocker et al, 2013;Cropper et al, 2014;deCastro et al, 2014;Jacox et al, 2014;Sydeman et al, 2014b;Varela et al, 2015) show results consistent with the findings of Sydeman et al (2014a). Those containing seemingly contradictory results (Demarcq, 2009;Dewitte et al, 2012) add uncertainty, but do not refute the findings of the metaanalysis, as they focus on local regions, use short time series and do not add uncertainty.…”
Section: Trends In Upwelling-favorable Windssupporting
confidence: 58%
“…Importantly, there is stronger agreement that significant trends of upwelling intensification are evident at higher latitude for all EBUS. Among studies excluded from the meta-analysis, either because they did not meet the strict selection criteria or because they were published after the analysis was completed, most (Di Lorenzo et al, 2005;Alves and Miranda, 2013;Barton et al, 2013;Bylhouwer et al, 2013;Stocker et al, 2013;Cropper et al, 2014;deCastro et al, 2014;Jacox et al, 2014;Sydeman et al, 2014b;Varela et al, 2015) show results consistent with the findings of Sydeman et al (2014a). Those containing seemingly contradictory results (Demarcq, 2009;Dewitte et al, 2012) add uncertainty, but do not refute the findings of the metaanalysis, as they focus on local regions, use short time series and do not add uncertainty.…”
Section: Trends In Upwelling-favorable Windssupporting
confidence: 58%
“…Moreover, they are in agreement with the changes observed during the last few decades; for example, Alves and Miranda (2013) found marked differences between open-sea and coastal trends when running an ORCM forced by ERA-40 and ERAInterim reanalyses and attributed these differences to an intensification of the upwelling system. The differences between the northern and southern sectors of the Iberian margin have also been reported by several authors: Relvas et al (2009) analysed different SST data sets spanning the last few decades and found an intensification of the upwelling in the southern sector of the Iberian margin, particularly in summer and autumn; and Álvarez et al (2008) analysed QuikSCAT and PFEL data and attributed the spatial differences in the upwelling system to the interaction between the macroscopic wind regime and coastal orography.…”
Section: On the Patterns Of Sst And Sss Projectionssupporting
confidence: 76%
“…It has been shown that CLLJ can also occur along the north coast of Spain, where some recent studies have proved that upwelling is a relatively common event, with particularly higher occurrence in the summer months (Alvarez et al, , 2010Alves and Miranda, 2013). Nevertheless, and in spite of the evidence of the existence of upwelling currents and offshore Ekman transport in the Iberian coast, to the authors' knowledge no detailed study of the wind regime in that coastal area has been pursuit.…”
Section: Discussionmentioning
confidence: 90%